Five faces of presidential governance: insights from policy-making in democratic Brazil. (4th May 2017) - Fenwick, Tracy B.; Burges, Sean W.; Power, Timothy J.
ABSTRACT: By drawing on the five Brazilian case studies presented in this special issue, we propose five 'faces' of presidentialism as a guide for examining the role of president in the public policy process: face to the general public; face to the bureaucracy; face to the subnational executives; face to congressional coalitions; and face to the outside world. How effectively the president succeeds in formulating and implementing their public policy priorities depends on their ability to execute the roles of each of these faces. A president's ability to successfully pursue their policy agenda is both constrained and facilitated by exogenous factors that impact the amount of attention, authority, and engagement that they are able to exert across the five faces they wear in the public policy process.